Durian Detection And Counting System Using Deep Learning - Amir Hilmi Ahmad Azizi; Izzudin Mat Lazim; Azween Mohd Rozmi; Sharma Roa Balakhrisnan; Fauzan Abdullah Ashaiman; Mus’ab Sahrim; Wan Zakiah Wan Ismail; Juliza Jamaludin; Irneza Ismail (Taylor’s University, Malaysia, 2024)
Indexed by Scopus/ERA/MyCite